2014
DOI: 10.1002/2014gl059214
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of double‐slope power spectra in the high‐latitude ionospheric plasma

Abstract: We report direct observations of the double‐slope power spectra for plasma irregularities in the F layer of the polar ionosphere. The investigation of cusp irregularities ICI‐2 sounding rocket, which was launched into the polar cusp ionosphere, intersected enhanced plasma density regions with decameter‐scale irregularities. Density measurements at unprecedented high resolution with multi‐Needle Langmuir Probes allowed for a detailed study of the plasma irregularities down to kinetic scales. Spectral analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
57
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 28 publications
11
57
0
Order By: Relevance
“…Since, the scintillations on the ground are due to the scattering of the GPS signals by the ionospheric irregularities and the interference when the radio waves propagate away from the irregular phase screen (Rino, 1979). Spicher et al (2014) reported that the electron density at high latitudes often shows double-slope power spectra. If we assume that the RFE was stationary in magnetic latitude during its lifetime, which was the situation for the current event, we can convert the data from a temporal scale to a spatial scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since, the scintillations on the ground are due to the scattering of the GPS signals by the ionospheric irregularities and the interference when the radio waves propagate away from the irregular phase screen (Rino, 1979). Spicher et al (2014) reported that the electron density at high latitudes often shows double-slope power spectra. If we assume that the RFE was stationary in magnetic latitude during its lifetime, which was the situation for the current event, we can convert the data from a temporal scale to a spatial scale.…”
Section: Discussionmentioning
confidence: 99%
“…The pierce point of GPS PRN30 moved southward at a speed of~66 m/s. Figure 3 of Spicher et al (2014). By using 1 km/s (the speed of the ICI-3 rocket), this spatial scale corresponds to a frequency range of 3-30 Hz in the low frequency part of the ICI-3 electron density power spectra.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such dual‐slope spectra indicate the presence of two different physical regimes, one where low‐frequency processes are dominating and another one where kinetic effects might be important. The double‐slope spectra in the high‐latitude F layer ionosphere had not been observed prior to Spicher et al [] presumably due to insufficient resolution in the previous experiments.…”
Section: Introductionmentioning
confidence: 87%
“…Using sounding rocket data, Spicher et al [] presented direct evidence of a steepening of the spectra at high frequencies in the polar regions, with the spectral knee close to the O + gyrofrequency. Such dual‐slope spectra indicate the presence of two different physical regimes, one where low‐frequency processes are dominating and another one where kinetic effects might be important.…”
Section: Introductionmentioning
confidence: 99%